A REVIEW OF FIQH MUAMALAH ON CONSUMER PROTECTION IN THE E-COMMERCE ERA: AN ANALYSIS OF PERSONAL DATA, REFUND POLICIES, AND STANDARD CLAUSES - Rizaldy Alpiansyah; Rohman Pranoto; Agus Salim; Miftah Wangsadanureja; Tatang Hidayat (Mutamayyiz: Journal of Islamic Studies, 2026)
The rapid growth of e-commerce in Indonesia brings economic efficiency but also creates major risks for consumers. These risks include the misuse of personal data, unfair refund policies, and one-sided standard contracts (adhesion contracts). This article examines these consumer protection issues by comparing Indonesian Positive Law with Fiqh Muamalah (Islamic Commercial Jurisprudence). Using a library research method, this study finds that cyber disputes mostly stem from gharar (uncertainty) and jahalah (lack of clear information). The analysis reveals that: (1) Islam views personal data protection as a sacred trust (amanah) to protect honor (hifz al-'irdh) and wealth (hifz al-mal). Data breaches are a transgression (ta'addi) that requires financial compensation and carries spiritual sanctions in the afterlife, a concept missing in state laws; (2) E-commerce refund policies use principles similar to the Islamic right of choice (khiyar). However, these policies are often unfair, either by forcing innocent buyers to pay return shipping or by letting bad-faith buyers exploit the system, which harms small sellers; (3) Standard contracts that free the platform from all liability are unjust. Although clicking "I agree" is a valid digital contract under Islamic law, hiding liability release clauses violates the principle of true mutual consent ('an taradin) and makes the contract void (fasid). Therefore, e-commerce platforms must create fair digital contracts and online dispute resolution systems based on mediation (shulh) to ensure mutual benefit.